2009
DOI: 10.1163/156853009x393747
|View full text |Cite
|
Sign up to set email alerts
|

Can Attitudes about Animal Neglect be Differentiated from Attitudes about Animal Abuse?

Abstract: Th e past decade has seen an increase in interest relating to the correlates and determinants of attitudes about nonhuman animals, especially attitudes about the use or abuse of animals. However, little research has explicitly addressed individual diff erences in attitudes about the neglect of animals. Th e current study employs a factor-analytic approach to explore (a) whether attitudes about animal neglect can be reliably diff erentiated from attitudes about animal abuse and (b) whether the relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…However, as Herzog (67) stresses, there is considerable overlap of distributions between the genders and often the variability between genders is less than the variability within genders. In addition to differences in the strength or direction of attitudes, Henry (34) identified structural differences between genders in their attitudes toward the treatment of animals, proposing that females had a broader recognition of what constituted cruelty than males.…”
Section: Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…However, as Herzog (67) stresses, there is considerable overlap of distributions between the genders and often the variability between genders is less than the variability within genders. In addition to differences in the strength or direction of attitudes, Henry (34) identified structural differences between genders in their attitudes toward the treatment of animals, proposing that females had a broader recognition of what constituted cruelty than males.…”
Section: Gendermentioning
confidence: 99%
“…Differences in attitudes and affection toward various species are well-documented in the literature [e.g., (32,33)] and as such, the target species is likely to be influential. Henry (34) found that exposure to animal mistreatment was related to decreased sensitivity or concern for the mistreatment of animals. As such, we could predict that people in areas of high rates of mistreatment (and therefore, more likely to witness mistreatment) would have less concern for the mistreatment of animals.…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of sociodemographic factors, in this research, it was observed that the female gender was an essential factor for adequate response in several items within the indicators, which may be related to the fact that women are generally the principal caregivers of companion animals and present a greater degree of attachment or connection to these animals, which was observed both by Ramo ´n et al (2010) [31] and Bures et al (2019) [37]. A study conducted by Henry et al (2009) [38] suggested that women are more empathetic towards animals than men, and even have a broader perception of what could be considered cruelty to animals. This could imply more excellent knowledge on the subject and greater interest in participating in this research, which may explain the predominance of females in the sample and the level of knowledge manifested by the studied population.…”
Section: Answersmentioning
confidence: 55%